FEAR OF NEGATIVE APPEARANCE EVALUATION TERHADAP CITRA TUBUH WANITA - IRMA ROSALINDA; NAOMI FRICILLA (Journal of Research and Measurement in Psychology, 2015)
The study was done to know the influence of fear of negative appearance evaluation toward body image of overweight women of late adolescene and early adulthood ages in Jakarta. Researcher used scale quantitatif methods psychology. Researcher used adapted instrument, namely MBRSQ-AS and FNAES. There are 108 samples of respondent which is overweight women of late adolescene and early adulthood ages. The data processing used in testing of hyphotheses analytics regression. The result of the influence is negative. It means that the higher fear of negative appearance evaluation the lower body image. The big influenced produced fear of negative appearance evaluation is 10,7% and the rest influenced by others.